MSME Business Feasibility Evaluation Model Based on Decision Management Perspective - Suandana, Ni Putu Widantari; Muni, Ni Made Jeni Apriliani (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2025)
MSMEs have an important role in the Indonesian economy, especially in Bali as an area known for its arts and culture industry. This research aims to develop an MSME business feasibility evaluation model using the Simple Additive Weighting (SAW) method. Six evaluation criteria are used, namely the level of product quality, the level of product damage, the level of market demand, the level of product diversity, the average monthly income, and the average operating costs. Data from seven MSMEs in Gianyar Bali were analyzed by the SAW method, resulting in a final score that determines the feasibility ranking. Results show that MSME C has the highest score (0.918), while MSME G has the lowest (0.741). The findings indicate that product quality and diversification are key success factors, while reducing operational costs is a challenge that needs attention. The SAW model provides a systematic approach for MSMEs to evaluate the viability of their businesses and support strategic decision-making.